Doing Justice to Recognition - Colish, Will (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
The traditional role of justice is to arbitrate where the good will of people is not enough, if even present, to settle a dispute between the concerned parties. It is a procedural approach that assumes a fractured relationship between those involved. Recognition, at first glance, would not seem to mirror these aspects of justice. Yet recognition is very much a subject of justice these days. The aim of this paper is to question the applicability of justice to the practice of recognition. The methodological orientation of this paper is a Kantian-style critique of the institution of justice, highlighting the limits of its reach and the dangers of overextension. The critique unfolds in the following three steps: 1) There is an immediate appeal to justice as a practice of recognition through its commitment to universality. This allure is shown to be deceptive in providing no prescription for the actual practice of this universality. 2) The interventionist character of justice is designed to address divided relationships. If recognition is only given expression through this channel, then we can only assume division as our starting ground. 3) The outcome of justice in respect to recognition is identification. This identification is left vulnerable to misrecognition itself, creating a cycle of injustice that demands recognition from anew. It seems to be well accepted that recognition is essential to justice, but less clear how to do justice to recognition. This paper is an effort in clarification.